Distribution of norovirus genotypes and P-types detected in patients with acute gastroenteritis attending two hospitals in Thailand. - Leera Kittigul (22676501) (2025)
(A) Detection rate of norovirus GII. (B) Monthly distribution of norovirus GII from December 2021 to March 2023.